2014
DOI: 10.1007/s11886-014-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with the Subcutaneous ICD

Abstract: The Subcutaneous Internal Cardiac Defibrillator (S-ICD) represents a major advance in the care of patients who have an indication for an internal cardiac defibrillator without pacing indications. Its main advantage is that it can deliver a shock to cardiovert ventricular arrhythmias utilising a tunnelled subcutaneous lead, negating the risks associated with conventional transvenous systems. Initial studies have shown comparable efficacy in cardioversion of induced and spontaneous ventricular tachycardia (VT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Implantation of an S-ICD is technically a novel procedure for cardiologists, thus new surgical skills are needed to be mastered [6,23,25,27]. All procedures were successfully performed in our population, which is consistent with the high success rate of S-ICD implantation reported by other authors [15,28]. The procedures performed in Poland were usually done by electrophysiologists, but in some centres the first few implantations were supported by cardiac or general surgeons.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Implantation of an S-ICD is technically a novel procedure for cardiologists, thus new surgical skills are needed to be mastered [6,23,25,27]. All procedures were successfully performed in our population, which is consistent with the high success rate of S-ICD implantation reported by other authors [15,28]. The procedures performed in Poland were usually done by electrophysiologists, but in some centres the first few implantations were supported by cardiac or general surgeons.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, in further experience published by one of the Polish centres the subcutaneous generator placement used at the beginning was then abandoned in favour of an intermuscular ap-proach [31]. Overall implantation time (mean: 84 ±14 min) was within the limits reported by others (mean: 45-101 min) [22,25,28].…”
Section: Discussionmentioning
confidence: 80%
“…Ongoing challenges with the S-ICD include T-wave oversensing and discrimination of AF with rapid ventricular rates from VT/VF in the VF zone. 139 Nevertheless, studies have shown similar rates of inappropriate shocks comparing the S-ICD system and standard transvenous ICD systems. At present, the S-ICD is an attractive option for patients in whom transvenous lead or septic complications are particularly likely to occur.…”
Section: New Defibrillator Technologiesmentioning
confidence: 99%
“…A S-ICD (nontransvenous) has been recently developed that avoids some of the problems associated with transvenous lead systems. 139 The S-ICD is placed in the left lateral position via a lateral submammary incision and the lead is tunneled to be positioned parasternally. Implant complications are minor and are usually due to wound infections that can be treated with antibiotics.…”
Section: New Defibrillator Technologiesmentioning
confidence: 99%
See 1 more Smart Citation